MENGOPTIMALKAN KESEHATAN FISIK DAN MENTAL MELALUI WORK LIFE BALANCE PADA OLAHRAGA KEBUGARAN INDONESIA (ORKI) TANGERANG - Melda Wiguna; Dede Andi; Siska Yunanti (Abdi Jurnal Publikasi, 2025)
Community Service (PKM) aims to optimize physical and mental health through the implementation of work-life balance within the Indonesian Fitness Sports Community (ORKI) in Tangerang. This activity is based on the need to raise public awareness about the importance of maintaining a balance between work and personal life to achieve holistic health. The methods employed include morning exercise, archery, and focus group discussions (FGDs), designed to strengthen participants' understanding of the close relationship between physical health, mental well-being, and life balance. The results of the activity demonstrate active participation and high enthusiasm from ORKI members, who not only gained an understanding of the importance of holistic health but also acquired new insights on managing time, involvement, and satisfaction in daily life. This activity strengthens the collaboration between Pamulang University and ORKI in promoting a healthy, productive lifestyle that benefits the community.